Enhancing Distraction Osteogenesis With Carbon Fiber Reinforced Polyether Ether Ketone Bone Pins and a Three-Dimensional Printed Transfer Device to Permit Artifact-Free Three-Dimensional Magnetic Resonance Imaging. Issue 1 (January 2021) - Eley, Karen A.; Moazen, Mehran; Delso, Gaspar; Javidan, Maryam; Kaggie, Joshua; Kalaskar, Deepak M.; Knowles, Jonathan C.; Owji, Nazanin; Watt-Smith, Stephen R.
Abstract : Objectives: To: (1) design an artifact-free 3D-printed MR-safe temporary transfer device, (2) engineer bone-pins from carbon fiber reinforced polyether ether ketone (CFR-PEEK), (3) evaluate the imaging artifacts of CFR-PEEK, and (4) confirm the osteointegration potential of CFR-PEEK, thus enhancing 3D-planning of bony advancements in hemifacial microsomia using sequential magnetic resonance imaging (MRI). Study Design: Engineered CRF-PEEK bone pins and a 3D printed ex-fix device were implanted into a sheep head and imaged with MRI and computed tomography . The osseointegration and bony compatibility potential of CFR-PEEK was assessed with scanning electron microscopy images of MC3T3 preosteoblast cells on the surface of the material. Results: The CFR-PEEK pins resulted in a signal void equivalent to the dimension of the pin, with no adjacent areas of MR-signal loss or computed tomography artifact. MCT3 cells adhered and proliferated on the surface of the discs by forming a monolayer of cells, confirming compatibility and osseointegration potential. Conclusion: A 3D printed transfer device could be utilized temporarily during MRI to permit artifact-free 3D planning. CFR-PEEK pins eliminate imaging artifact permitting sequential MRI examination. In combination, this has the potential to enhance distraction osteogenesis, by permitting accurate three-dimensional planning without ionizing radiation. Abstract : Supplemental Digital Content is available in the text